Half-isomorphisms of Finite Automorphic Moufang Loops. Issue 10 (2nd October 2016) - Grishkov, A.; Merlini Giuliani, M. L.; Rasskazova, M.; Sabinina, L.
Abstract : We show that each half-automorphism of a finite automorphic Moufang loop is trivial. In general, this is not true for finite left automorphic Moufang loops and for finite automorphic loops.